Feature Papers in Compounds - Mejuto, Juan C. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book represents a collection of contributions in the field of the synthesis and characterization of chemical compounds, natural products, chemical reactivity, and computational chemistry. Among its contents, the reader will find high-quality, peer-reviewed research and review articles that were published in the open access journal Compounds by members of the Editorial Board and the authors invited by the Editorial Office and Editor-in-Chief.